The impact of post-encoding alcohol consumption on episodic memory recall and remember-know responses in heavy drinkers - Butterworth, Benjamin; Hand, Christopher James; Lorimer, Karen; Gawrylowicz, Julie (Frontiers in Psychology, 2023)
People often consume alcohol following trauma, particularly in response to distressing memories (Dixon et al., 2009). To date, little is known about how post-encoding alcohol consumption influences episodic memory recall for negative events. Understanding these effects may help to improve support for trauma victims – for example, witnesses and victims of crimes. We tested 60 participants who self-described as heavy drinkers. After watching an analogue trauma film, half were allocated to consuming a moderate dose of alcohol (Alcohol-Exposed group), while half received a placebo drink (Placebo-Control group). Immediately and after a one-week delay, participants recalled the event via free and cued recall tasks. Participants also gave remember-know responses and confidence ratings, elucidating alcohol’s effect on experiential memory. Free recall performance was similar for the Alcohol-Exposed group and the Placebo-Control group during Sessions 1 and 2. The Alcohol-Exposed group benefitted more from the delayed repeated retrieval attempt. For the cued recall task, the Alcohol-Exposed group provided more “Don’t Know” responses compared to the Placebo-Control group in both sessions. For the Alcohol-Exposed group only “Correct Know” responses increased from Session 1 to 2. Although memory performance improved across sessions, confidence levels decreased from Session 1 to 2 in the Alcohol-Exposed group. Post-encoding alcohol consumption appears to impact immediate episodic memory retrieval; however, this effect is only temporary in nature. No evidence was found that alcohol primarily reduces remembering responses. Much like previous findings focusing on pre-encoding alcohol consumption (Hagsand et al., 2017), current findings suggest that providing individuals who drank alcohol after witnessing an incident with a delayed repeated retrieval attempt can lead to more complete and accurate testimonies.